Sizing material for edge sealing strip of new energy battery and preparation method of sizing material
By using ethylene propylene ternary rubber, graphene powder and other materials in the rubber for battery edge sealing strips, and preparing composite materials, combined with the mixing and glue discharging technology of the mixer, the problem of insufficient performance of the existing rubber is solved. , achieving improved performance such as hardness, tensile strength, ozone resistance, and higher safety.
Patent Information
- Application Number
- CN202411350731.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-07
AI Technical Summary
While the existing rubber for battery edge sealing strips increases hardness, tensile strength, tear elongation, and tear strength, it is difficult to simultaneously improve the compression permanent deformation performance, ozone resistance, high and low temperature resistance and copper corrosion resistance. , and there are problems with toxicity and contamination of vulcanizing agents.
A new energy battery edge sealing rubber, including ethylene propylene rubber, graphene powder, heavy calcium, light calcium, paraffin oil, nano silica, stearic acid, melamine-urea-glucose and additives , by preparing graphene powder/nano silica/melamine-urea-glucose composite, combined with other materials, kneading and discharging through a mixer, the glue with excellent performance was obtained.
The hardness of the rubber is between 70.6-73.5 Shore A, tensile strength >17MPa, tear elongation >388%, tear strength ≥25kgf/cm, compression permanent deformation heat ≤22, ozone resistance, high and low resistance Gentle copper corrosion resistance, excellent performance, suitable for use in new energy battery edge sealing strips, and does not use sulfur, making it safer.
Smart Images

Figure BDA0005062288830000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rubber materials for battery edge banding strips, and in particular to a rubber material for new energy battery edge banding strips and a preparation method thereof. Background Art
[0002] As one of the core components of new energy vehicles, the development of power batteries has a great impact on the development of new energy vehicles. Based on the needs of safety, management, maintenance and replacement, power lithium batteries must be encapsulated in certain containers before they can be installed on vehicles. Rubber, as a sealing material, is indispensable in battery packaging. Its excellent sealing performance is the key to ensuring the isolation of the internal space of the battery from the external space during use, and preventing various impurities, rainwater, air, and dust from entering the battery and damaging the battery to cause accidents.
[0003] Ethylene propylene rubber is a copolymer of ethylene, propylene and a small amount of non-conjugated diene, represented by EPDM (Ethylene Propylene Diene Monomer). Because its main chain is composed of chemically stable saturated hydrocarbons and only contains unsaturated double bonds in the side chains, it has excellent aging resistance such as ozone resistance, heat resistance, weather resistance, etc.
[0004] However, in order to improve the performance and durability of rubber, vulcanizers (such as CN114196124A, etc.) are often added to the components, which has great toxicity and pollution problems. In addition, the comprehensive performance of the rubber compound still needs to be further improved. It is necessary to develop a rubber compound for new energy battery edge banding with high hardness, tensile strength, elongation at break, tear strength, compression permanent deformation performance, ozone resistance, high and low temperature resistance, and copper corrosion resistance.
[0005] Based on this, the present invention designs a rubber material for new energy battery edge banding strips and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a rubber material for new energy battery edge banding and a preparation method thereof.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A rubber material for edge banding of new energy batteries comprises the following raw materials in parts by weight: 79-119 parts of EPDM rubber, 110-140 parts of graphene powder, 26-46 parts of heavy calcium carbonate, 16-36 parts of light calcium carbonate, 48-68 parts of paraffin oil, 4-8 parts of nano silicon dioxide, 0.5-2 parts of stearic acid, 10-15 parts of melamine-urea-glucose (MUG), and 4.6-12.8 parts of additives.
[0009] Furthermore, the EPDM rubber comprises the following raw materials in parts by weight: 56-76 parts of EPDM rubber 3110M and 23-43 parts of EPDM rubber 5601.
[0010] Furthermore, the auxiliary agent includes the following raw materials in parts by weight: 1.5-3 parts of active agent, 0.5-2 parts of antioxidant, 2.5-7.5 parts of accelerator, and 0.1-0.3 parts of anti-scorch agent.
[0011] Furthermore, the paraffin oil uses 48-68 parts of paraffin oil MP100H, the antioxidant uses 0.5-2 parts of antioxidant KY-405, the activator uses 1.5-3 parts of activator PEG4000; and the anti-scorch agent uses 0.1-0.3 parts of anti-scorch agent E / C-80.
[0012] Furthermore, the accelerator includes the following raw materials in parts by weight: 0.5-1.5 parts of accelerator BZ-80, 0.5-1.5 parts of accelerator CZ-80, 0.5-1.5 parts of accelerator DTDM-80, 0.5-1.5 parts of accelerator TRA-70, and 0.5-1.5 parts of accelerator M-800.
[0013] Furthermore, the mass ratio of EPDM rubber, nano-silica, and melamine–urea–glucose (MUG) is 99:6:0.2:12.5.
[0014] Furthermore, the particle size of the graphene powder is 100-200 μm.
[0015] In order to better achieve the purpose of the present invention, the present invention also provides a method for preparing the rubber material for the edge banding strip of the new energy battery, comprising the following steps:
[0016] 1) Preparing graphene powder / nano-silicon dioxide / melamine-urea-glucose composite;
[0017] Graphene powder and nano-silicon dioxide are mixed at 105-114°C, cooled to 40°C, melamine-urea-glucose is added dropwise, and then stearic acid is added. The mixture is stirred at 2000-2500 r / min for 1-2 hours.
[0018] 2) In the first stage of mixing, the EPDM rubber is put into an internal mixer and mixed for 40-50 seconds, and then heavy calcium, light calcium, paraffin oil, activator, antioxidant, and anti-scorch agent are added and mixed for 80-100 seconds;
[0019] 3) In the second stage of mixing, the material after the first stage of mixing is added with the accelerator, mixed for 80-100 seconds and then discharged to obtain the product.
[0020] Furthermore, the mixing pressure is 10-12 MPa, the mixing chamber temperature is 37-43°C, and the debinding temperature is 104-106°C.
[0021] In order to better achieve the purpose of the present invention, the present invention also provides a rubber material for new energy battery edge banding strips prepared by the preparation method, the hardness of the rubber material for new energy battery edge banding strips is 70.6-73.5A, tensile strength is greater than 17MPa, elongation at break is greater than 388%, tear strength is ≥25kgf / cm; compression permanent deformation heat is ≤22, ozone resistance is 40℃×70h×100pphm×20% stretching×60% humidity without cracks, low temperature resistance is -40℃*3.0min without cracks, and copper corrosion resistance is 100℃×24h without coloring.
[0022] Compared with the prior art, the present invention has the following beneficial effects: the hardness of the rubber material of the present invention is between 70.6-73.5 Shore A, the tensile strength is greater than 17MPa, the elongation at break is greater than 388%, and the tear strength is greater than or equal to 25kgf / cm; at the same time, the compression permanent deformation heat (70℃*24h) is ≤22, the ozone resistance is 40℃×70h×100pphm×20% stretching×60% humidity without cracks, the low temperature resistance is -40℃*3.0min without cracks, and the copper corrosion resistance is 100℃×24h without coloring. It has excellent basic physical properties, good compression permanent deformation performance, good ozone resistance, excellent high and low temperature resistance, and strong copper corrosion resistance, and is suitable for use as a rubber material for edge banding of new energy batteries.
[0023] The present invention first prepares the graphene powder / nano silicon dioxide / melamine-urea-glucose composite material, and then combines it with other materials to enhance the tensile strength, elongation at break, tear strength, compression permanent deformation, ozone resistance, copper corrosion resistance, etc. At the same time, sulfur is not used, which is safer. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1: In some embodiments, a rubber material for edge banding of new energy batteries includes the following raw materials in parts by weight: 56 parts of EPDM 3110M, 143 parts of EPDM 560, 110 parts of graphene powder, 26 parts of heavy calcium, 16 parts of light calcium, 48 parts of paraffin oil MP100H, 4 parts of nano-silicon dioxide, 0.5 parts of stearic acid, 0.5 parts of antioxidant KY-405, 1.5 parts of active agent PEG4000, 0.5 parts of accelerator BZ-80, 0.5 parts of accelerator CZ-80, 0.5 parts of accelerator DTDM-80, 0.5 parts of accelerator TRA-70, 0.5 parts of accelerator M-80, 10 parts of melamine-urea-glucose (MUG), and 0.1 parts of anti-scorch agent E / C-80. The particle size of the graphene powder is 100 μm.
[0026] The method for preparing the rubber material for the edge banding strip of the new energy battery comprises the following steps:
[0027] 1) Preparing graphene powder / nano-silicon dioxide / melamine-urea-glucose composite;
[0028] Graphene powder and nano-silica were mixed at 105°C, cooled to 40°C, and melamine-urea-glucose was added dropwise. After the addition, stearic acid was added and stirred at 2000 r / min for 1 h.
[0029] 2) In the first stage of mixing, EPDM rubber is put into an internal mixer and mixed for 40 seconds, and then heavy calcium, light calcium, paraffin oil, activator, antioxidant, and anti-scorch agent are added and mixed for 80 seconds. The mixing pressure is 10 MPa and the mixing chamber temperature is 37°C;
[0030] 3) In the second stage of mixing, the material after the first stage of mixing is added with the accelerator, and the binder is discharged after mixing for 80 seconds. The mixing pressure is 10 MPa, the mixing chamber temperature is 37° C., and the discharge temperature is 104° C. to obtain the product.
[0031] Embodiment 2: In some embodiments, a rubber material for edge banding of new energy batteries includes the following raw materials in parts by weight: 76 parts of EPDM 3110M, 123 parts of EPDM 560, 140 parts of graphene powder, 46 parts of heavy calcium, 36 parts of light calcium, 68 parts of paraffin oil MP100H, 8 parts of nano silicon dioxide, 2 parts of stearic acid, 52 parts of antioxidant KY-40, 3 parts of active agent PEG4000, 1.5 parts of accelerator BZ-80, 1.5 parts of accelerator CZ-80, 1.5 parts of accelerator DTDM-80, 1.5 parts of accelerator TRA-70, 1.5 parts of accelerator M-80, 15 parts of melamine-urea-glucose (MUG), and 0.3 parts of anti-scorch agent E / C-80. The particle size of the graphene powder is 200 μm.
[0032] The method for preparing the rubber material for the edge banding strip of the new energy battery comprises the following steps:
[0033] 1) Preparing graphene powder / nano-silicon dioxide / melamine-urea-glucose composite;
[0034] Graphene powder and nano-silica were mixed at 114°C, cooled to 40°C, melamine-urea-glucose was added dropwise, and stearic acid was added after the addition, and the mixture was stirred at 2500 r / min for 2 h.
[0035] 2) In the first mixing stage, EPDM rubber is put into an internal mixer and mixed for 50 seconds, and then heavy calcium, light calcium, paraffin oil, activator, antioxidant, and anti-scorch agent are added and mixed for 100 seconds. The mixing pressure is 12 MPa and the mixing chamber temperature is 43°C.
[0036] 3) In the second stage of mixing, the material after the first stage of mixing is added with the accelerator, and the binder is discharged after mixing for 100 seconds. The mixing pressure is 12 MPa, the mixing chamber temperature is 43° C., and the binder discharge temperature is 106° C. to obtain the product.
[0037] Embodiment 3: In some embodiments, a rubber material for edge banding of new energy batteries includes the following raw materials in parts by weight: 66 parts of EPDM 3110M, 133 parts of EPDM 560, 125 parts of graphene powder, 36 parts of heavy calcium, 26 parts of light calcium, 58 parts of paraffin oil MP100H, 6 parts of nano-silicon dioxide, 1.25 parts of stearic acid, 1.25 parts of antioxidant KY-405, 2.25 parts of active agent PEG4000, 1 part of accelerator BZ-80, 1 part of accelerator CZ-80, 1 part of accelerator DTDM-80, 1 part of accelerator TRA-70, 1 part of accelerator M-80, 12.5 parts of melamine-urea-glucose (MUG), and 0.2 parts of anti-scorch agent E / C-80. The particle size of the graphene powder is 150 μm.
[0038] The method for preparing the rubber material for the edge banding strip of the new energy battery comprises the following steps:
[0039] 1) Preparing graphene powder / nano-silicon dioxide / melamine-urea-glucose composite;
[0040] Graphene powder and nano-silica were mixed at 108°C, cooled to 40°C, and melamine-urea-glucose was added dropwise. After the addition, stearic acid was added and stirred at 2200 r / min for 1.6 h.
[0041] 2) In the first mixing stage, EPDM rubber is put into an internal mixer and mixed for 45 seconds, and then heavy calcium, light calcium, paraffin oil, activator, antioxidant, and anti-scorch agent are added and mixed for 90 seconds. The mixing pressure is 11 MPa and the mixing chamber temperature is 40°C;
[0042] 3) In the second stage of mixing, the material after the first stage of mixing is added with the accelerator, and the binder is discharged after mixing for 90 seconds. The mixing pressure is 11 MPa, the mixing chamber temperature is 38° C., and the discharge temperature is 105° C. to obtain the product.
[0043] Comparative Example 1: In some embodiments, a rubber material for edge banding of new energy batteries includes the following raw materials in parts by weight: 66 parts of EPDM 3110M, 133 parts of EPDM 560, 125 parts of graphene powder, 36 parts of heavy calcium, 26 parts of light calcium, 58 parts of paraffin oil MP100H, 6 parts of nano-silicon dioxide, 1.25 parts of stearic acid, 1.25 parts of antioxidant KY-405, 2.25 parts of active agent PEG4000, 1 part of accelerator BZ-80, 1 part of accelerator CZ-80, 1 part of accelerator DTDM-80, 1 part of accelerator TRA-70, 1 part of accelerator M-80, and 0.2 parts of anti-scorch agent E / C-80. The particle size of the graphene powder is 150 μm.
[0044] The method for preparing the rubber material for the edge banding strip of the new energy battery comprises the following steps:
[0045] 1) Preparing graphene powder / nano-silicon dioxide composites;
[0046] The graphene powder and nano-silicon dioxide were mixed at 108°C, cooled to 40°C, stearic acid was added, and stirred at 2200 r / min for 1.6 h;
[0047] 2) In the first mixing stage, EPDM rubber is put into an internal mixer and mixed for 45 seconds, and then heavy calcium, light calcium, paraffin oil, activator, antioxidant, and anti-scorch agent are added and mixed for 90 seconds. The mixing pressure is 11 MPa and the mixing chamber temperature is 40°C;
[0048] 3) In the second stage of mixing, the material after the first stage of mixing is added with the accelerator, and the binder is discharged after mixing for 90 seconds. The mixing pressure is 11 MPa, the mixing chamber temperature is 38° C., and the discharge temperature is 105° C. to obtain the product.
[0049] Test Case
[0050] The performance of the rubber materials of Examples 1-3 and Comparative Example 1 was tested, and the results are shown in Table 1.
[0051] Table 1 Performance test results
[0052]
[0053] It can be seen that the hardness of the rubber material of the present invention is between 70.6-73.5 Shore A, the tensile strength is greater than 17MPa, the elongation at break is greater than 388%, and the tear strength is greater than or equal to 25kgf / cm; at the same time, the compression permanent deformation heat (70℃*24h) is ≤22, the ozone resistance is 40℃×70h×100pphm×20% stretching×60% humidity without cracks, the low temperature resistance is -40℃*3.0min without cracks, and the copper corrosion resistance is 100℃×24h without coloring. It has excellent basic physical properties, good compression permanent deformation performance, good ozone resistance, excellent high and low temperature resistance, and strong copper corrosion resistance, and is suitable for use as a rubber material for edge banding of new energy batteries.
[0054] The present invention first prepares the graphene powder / nano silicon dioxide / melamine-urea-glucose composite material, and then combines it with other materials to enhance the tensile strength, elongation at break, tear strength, compression permanent deformation, ozone resistance, copper corrosion resistance, etc. At the same time, sulfur is not used, which is safer.
[0055] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A rubber material for edge banding of new energy batteries, characterized in that: The invention comprises the following raw materials in parts by weight: 79-119 parts of EPDM rubber, 110-140 parts of graphene powder, 26-46 parts of heavy calcium carbonate, 16-36 parts of light calcium carbonate, 48-68 parts of paraffin oil, 4-8 parts of nano silicon dioxide, 0.5-2 parts of stearic acid, 10-15 parts of melamine-urea-glucose (MUG) and 4.6-12.8 parts of additives.
2. The rubber material for edge banding of new energy batteries according to claim 1, characterized in that: The EPDM rubber comprises the following raw materials in parts by weight: 56-76 parts of EPDM rubber 3110M and 23-43 parts of EPDM rubber 5601.
3. The rubber material for edge banding of new energy batteries according to claim 2, characterized in that: The auxiliary agent comprises the following raw materials in parts by weight: 1.5-3 parts of active agent, 0.5-2 parts of antioxidant, 2.5-7.5 parts of accelerator and 0.1-0.3 parts of anti-scorch agent.
4. The rubber material for edge banding of new energy batteries according to claim 3, characterized in that: The paraffin oil uses 48-68 parts of paraffin oil MP100H, the antioxidant uses 0.5-2 parts of antioxidant KY-405, the activator uses 1.5-3 parts of activator PEG4000, and the anti-scorch agent uses 0.1-0.3 parts of anti-scorch agent E / C-80.
5. The rubber material for edge banding of new energy batteries according to claim 4, characterized in that: The accelerator comprises the following raw materials in parts by weight: 0.5-1.5 parts of accelerator BZ-80, 0.5-1.5 parts of accelerator CZ-80, 0.5-1.5 parts of accelerator DTDM-80, 0.5-1.5 parts of accelerator TRA-70, and 0.5-1.5 parts of accelerator M-800.
6. The rubber material for edge banding of new energy batteries according to claim 5, characterized in that: The mass ratio of EPDM rubber, nano-silica, and melamine-urea-glucose (MUG) is 99:6:0.2:12.
5.
7. The rubber material for edge banding of new energy batteries according to claim 6, characterized in that: The particle size of graphene powder is 100-200 μm.
8. A method for preparing a rubber material for edge banding of new energy batteries according to claim 7, characterized in that: The following steps are involved: 1) Preparing graphene powder / nano-silicon dioxide / melamine-urea-glucose composite; Graphene powder and nano-silicon dioxide are mixed at 105-114°C, cooled to 40°C, melamine-urea-glucose is added dropwise, and then stearic acid is added. The mixture is stirred at 2000-2500 r / min for 1-2 hours. 2) In the first stage of mixing, the EPDM rubber is put into an internal mixer and mixed for 40-50 seconds, and then heavy calcium, light calcium, paraffin oil, activator, antioxidant, and anti-scorch agent are added and mixed for 80-100 seconds; 3) In the second stage of mixing, the material after the first stage of mixing is added with the accelerator, mixed for 80-100 seconds and then discharged to obtain the product.
9. The method for preparing the rubber material for the edge banding of new energy batteries according to claim 8, characterized in that: The mixing pressure is 10-12MPa, the mixing chamber temperature is 37-43℃; the debonding temperature is 104-106℃.
10. A rubber material for edge banding of new energy batteries prepared by the preparation method according to claim 9, characterized in that: The hardness of the rubber material used for the edge banding strip of the new energy battery is 70.6-73.5A, the tensile strength is greater than 17MPa, the elongation at break is greater than 388%, the tear strength is ≥25kgf / cm; the compression permanent deformation heat is ≤22, the ozone resistance is 40℃×70h×100pphm×20% stretching×60% humidity without cracks, the low temperature resistance is -40℃*3.0min without cracks, and the copper corrosion resistance is 100℃×24h without coloring.
Citation Information
Patent Citations
Ethylene-propylene-diene monomer rubber
CN114196124A